PENGARUH MODEL PEMBELAJARAN SSCS TERINTEGRASI STRATEGI MERINGKAS TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK DI KELAS XII - Maresti Feronika Tanaem; Yusnaeni Yusnaeni; Arini Rahma Dhani; Moses Kopong Tokan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to determine the improvement in students' scientific literacy through the implementation of the SSCS learning model integrated with a summarizing strategy among Grade XII students at SMA Negeri Harekakae during the 2025/2026 academic year. A quasi-experimental research design—specifically a pretest-posttest control group design involving two classes—was employed. The sample was selected using a random sampling technique. The research instrument consisted of a 20-item multiple-choice test covering scientific literacy indicators: identifying scientific problems, interpreting data and drawing conclusions, understanding science concepts, and applying science concepts in real-life situations. The collected data were analyzed using both descriptive and inferential statistics. The results indicated that the normality test values for the experimental class's pretest and posttest were 0.004 (< 0.05) and 0.001 (< 0.05), respectively, while the homogeneity test values for the control and experimental classes' pretests were 0.106 (> 0.05) and 0.028 (< 0.05); thus, the data were neither normally distributed nor homogeneous. Consequently, the analysis proceeded using a non-parametric test, specifically the Mann-Whitney Test. Posttest results showed an average score of 7.76 for the control class and 13.05 for the experimental class, demonstrating that the SSCS learning model integrated with a summarizing strategy had an effect on improving students' scientific literacy.